KEANEKARAGAMAN FUNGI MIKORIZA ARBUSKULA PADA BEBERAPA TIPE PEMANFAATAN LAHAN GAMBUT DI DESA RASAU JAYA KABUPATEN KUBU RAYA - Dwi Zulfita; Surachman; Putu Dupa Bandem; Eddy Santoso (Program Studi Agroteknologi INSTIPER, 2018)
This study aims to determine the diversity of FMA from rhizosphere of cassava, corn, taro and peanut cultivated on peat lands of Rasau Jaya village by using a corn plant host. The research was conducted at the Biology and Soil Biotechnology Laboratory of the Faculty of Agriculture and plastic housings in the experimental garden of the Faculty of Agriculture Untan and lasted from 26 April 2017 until the date of September 15, 2017. The research procedure was carried out by taking samples of soil and roots from the rhizosphere of cassava, corn, taro and peanuts cultivated in peat lands. Soil and root sampling in each rhizosphere was performed at 4 points of observation as replication with a depth of 0-20 cm and a diameter of 20 cm and then put into plastic bags and labeled. The soil samples taken are then used for microscopic analysis (extraction and identification) and soil analysis to determine the chemical properties. Root samples were stained to determine the percentage of colonization. Trapping culture uses corn crops. Furthermore, extraction and spore identification were performed using the same technique with the extraction and identification of soil samples. Observed variables were including percentage of root colonization, spore density, and spore diversity. The results showed that FMA diversity from 4 types of peat land use from rhizosphere of cassava, corn, taro and peanut plants in Rasau Jaya village before and after trapping showed an increase of spore, diversity of FMA type, while the percentage of infected root values showed variation. Observations on the number of spores showed an increase from 37 to 62 per 50 g of soil increased to 60-170 spores per 50 g of soil. Spore type diversity of 10 Glomus types, 1 type of Gigaspora and 4 types of Acaulospora into 13 Glomus types, 3 types of Gigaspora and 4 types of Acaulospora. The highest percentage of infected roots before trapping ranged between 46.89% - 73.33% and after trapping ranged between 77.89% - 95.50%. Keywords: Arbuscular Mycorrhiza Fungi, diversity, peat lands